Making a meal for a gnome - Owen, Ruth, 1967- (Minneapolis, Minnesota : Bearport Publishing Company, 2022)
"What do you make to feed a hungry gnome that stops by for dinner? A meal that's delicious for your guest and for you! First up, make a tasty forest berry smoothie and some deviled eggs with funny gnome faces as a crowd-pleasing appetizer. Then, celebrate your guest's gnome relatives by serving traditional Cornish pasties. To top of your magnificent meal, finish with a tree branch dessert (also known as a delicious chocolate cake wrapped up to remind your friend of their woodsy home). Don't forget to explore gnome myths so you have plenty to talk about during your mythical meal"--
Includes bibliographical references and index.
Ages 7-10
Grades 2-3
Keywords: Cooking -- Juvenile literature; Cookbooks